Effects of a unit of mime based on the Sports Education model on interculturality - Méndez-Giménez, A.; Puente-Maxera, F.; Martínez de Ojeda Pérez, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aim of this study was to assess the impact of a Sport Education unit on elementary school students’ intercultural competence. The program involved the participation of 28 fifth-grade students (M = 10.75; DT = .75) from a state school in Region of Murcia, Spain.A quasi-experimental design, pretest and posttest (of quantitative and qualitative nature) measures, was used. The data included students’ questionnaires and interviews, andteachers’ interviews and diary notes. Results indicated that students improved on positive emotional responses, as well as providing help and having better relations with their peers from different cultures/countries. The incidence of methodological elements, communication and the social climate of the classroom on the development of intercultural competence is also discussed. Lines of future research are suggested in order to improve the model for the development of intercultural competence.